2011
DOI: 10.1089/ham.2009.1094
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation in Healthy Children Aged 5 to 16 Years Residing in Huayllay, Peru at 4340 m

Abstract: Schult, Sandra, and Carlos Canelo-Aybar. Oxygen saturation in healthy chidren aged 5 to 6 years residing in Huayllay, Peru, at 4340 m. High Alt. Med. Biol. 12:89-92, 2011.-Hypoxemia is a major life-threatening complication of childhood pneumonia. The threshold points for hypoxemia vary with altitude. However, few published data describe that normal range of variation. The purpose of this study was to establish reference values of normal mean Sao 2 levels and an approximate cutoff point to define hypoxemia for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
2
10
1
1
Order By: Relevance
“…Anthropometry z score distributions were normal after removing a single strong outlier, and similarly for S p O 2 after excluding two individuals with unusually low readings. Despite previous studies reporting an association between S p O 2 and age (Schult and Canelo-Aybar, 2011), no such relationship was found in our data (Pearson’s correlation, P  = 0.1). Sex differences in S p O 2 were also absent ( t -test, P  = 0.3).…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…Anthropometry z score distributions were normal after removing a single strong outlier, and similarly for S p O 2 after excluding two individuals with unusually low readings. Despite previous studies reporting an association between S p O 2 and age (Schult and Canelo-Aybar, 2011), no such relationship was found in our data (Pearson’s correlation, P  = 0.1). Sex differences in S p O 2 were also absent ( t -test, P  = 0.3).…”
Section: Methodscontrasting
confidence: 99%
“…S p O 2 represents only one component of blood oxygen content (the total amount of oxygen the blood carries) which is also a function of erythrocyte and hemoglobin concentrations (Beall, 2001,2007). The advantage of S p O 2 is that it can be measured simply, inexpensively and non-invasively by pulse oximetry (Schult and Canelo-Aybar, 2011), and evidence for a major gene among Tibetans that increases oxygen saturation (Beall et al, 1994,1997) demonstrates that S p O 2 is sufficiently important to have been under natural selection in this native high altitude population. However, Andeans do not seem to share this adaptation (Beall et al, 2004).…”
mentioning
confidence: 99%
“…Another potential cofounding factor is that our study took place in altitude; many studies have showed lower mean oxygen saturation in wake and sleep states at high altitudes in adults and neonates [49,50]. By incorporating an oxygen saturation nadir into a severity scale, one would anticipate more patients will be diagnosed with severe OSA in our sample compared to a population of patients at sea level due to the lower partial pressure of oxygen at altitude.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Orta rakımlı yerlerde SO 2 biraz daha düşüktür (ortalama %97-98, -2SD %93-96) ve yüksek rakımlara çıkıldıkça daha da azalır (>3.000 m; ortalama %86-91, -2SD %74-82). 5,6,[10][11][12] Çocukların çoğunun SO 2 değerleri, 24 saat içinde ilerleyici bir dalgalanma gösterir. En düşük değerler sabah erken saatlerde görülürken; en yük-sek değerler akşamüstü saatlerinde görülür.…”
Section: Normal Değerlerunclassified